Completeness of Medical Records Documents with Diagnosis of Bronchial Asthma in Outpatients at Pondok Kopi Islamic Hospital Jakarta - Mutiara Shiffa Indah Cahyani (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2025)
Completeness of medical record documents is the assessment or review of documents, and contents of medical records related to documentation, services and/or assessing the completeness of medical records. Medical records are written or recorded information or notes regarding identity, which contain 1). Notes, which include a description of the patient's identity, patient examination, diagnosis results, treatment, actions and other services carried out by doctors, dentists or other health workers according to their competence; 2). Documents, which are complete records, include x-ray photos, laboratory results and other information by scientific competence. Types of medical records consist of conventional medical records; and electronics. Medical Records can be stored alphabetically and numerically. The record management process is carried out by Medical Records officers at the Hospital at RSIJ Pondok Kopi Jakarta starting from the stage of preparing the Medical Record document (Assembling), the Indexing process (list of illnesses, actions, doctors and deaths), Quantitative analysis of medical records (Analysing) and finally storage of medical records according to the applicable alignment system (Filling). The factors that influence incomplete medical records are: 1). HR; 2). Tools/Machines; 3). Method/Method; 3). Material; and 4) Finance/Money.